PERANCANGAN APLIKASI PENILAIAN RUMAH TIDAK LAYAK HUNI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING PADA KEGIATAN KEMENTERIAN PUPR - Faisal Ruswanto; Herry Wahyono; Ali Khumaidi (TEKNOKRIS, 2023)
Determination of recipients of uninhabitable housing assistance (RTLH) is one of the problems that is of concern to the Directorate of Self-Help Housing of the Ministry of Public Works and Public Housing of the Republic of Indonesia, because the large number of data on incoming aid proposals makes it difficult to determine which beneficiaries deserve due to the limited budget. One way to determine beneficiaries is to use a decision system using the Simple Additive Weighting (SAW) method. This method will provide the value of the selected alternative preference as an indicator to determine the recipient of assistance as it can help the data processing team, stakeholders and leaders in the Directorate of Self-Help as the government which has a policy in determining the prospective recipients of the house renovation assistance objectively not subjectively. The data used was taken from data collection conducted by the field team in the Serang City area of Banten Province where the data obtained were 935 residents